"Convivência" Groups: Building Active and Healthy Communities of Older Adults in Brazil. (8th July 2012) - Benedetti, Tânia R. Bertoldo; d'Orsi, Eleonora; Schwingel, Andiara; Chodzko-Zajko, Wojtek J.
Abstract : In old age, social groups can be a crucial component for health and well-being. In 2009-2010, a follow-up survey was carried out in Florianópolis, Brazil to understand the impact of a variety of programs established since 2002 that were designed to enhance social activities among the older adult population. This study employed two surveys within the population of older adults in Florianópolis. The first survey interviewed a total of 875 older adults in 2002, and the second survey involved 1, 705 older adults between 2009 and 2010. By 2010, many new programs were offered in the community and the enrollment of older adults in social programs followed similar trends. "Convivência" groups stood out as extremely popular social groups among this population. This paper discusses some of the potential outcomes associated with participation in "convivência" groups.